An isolated mass-gap black hole or neutron star detected with astrometric microlensing (2022, ApJL, 933, L23) - Lam, Casey; Lu, Jessica R.; Udalski, Andrzej; Bond, Ian; Bennett, David P.; Skowron, Jan; Mróz, Przemek; Poleski, Radek; Sumi, Takahiro; Szymański, Michał K.; Koz\lowski, Szymon; Pietrukowicz, Paweł; et al. (The astrophysical journal. Supplement series, 2022)
This supplement provides supporting material for Lam et al. We briefly summarize past gravitational microlensing searches for black holes (BHs) and present details of the observations, analysis, and modeling of five BH candidates observed with both ground-based photometric microlensing surveys and Hubble Space Telescope astrometry and photometry. We present detailed results for four of the five candidates that show no or low probability for the lens to be a BH. In these cases, the lens masses are <2 M ⊙, and two of the four are likely white dwarfs or neutron stars. We also present detailed methods for comparing the full sample of five candidates to theoretical expectations of the number of BHs in the Milky Way (∼108).